Boundary integral equations for problems about plane deformations of linear viscotlastic medium - Zinkevych, Oleksiy; Neschadym, Alexander; Safonov, Vladimir (My University, 2013)
We solve the problem of building a system of boundary integral equations for the density visco-elastic potentials, which is used in the determination of the displacement vector of a viscoelastic medium.
Keywords: viscoelastic-plastic systems; в'язко-пружно-пластичні системи; інтегральні рівняння; integral equations; кафедра вищої математики імені проф. Можара В. І.